2018
DOI: 10.1111/aje.12501
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance rate of chimpanzee scats: Implications for census work on Pan troglodytes

Abstract: Scat (faeces) decay rate estimates are used to calculate animal species abundance and density. For African great apes, this has been measured only for Gorilla; chimpanzee scats are assumed to decay at a faster rate due to lower fibre content. We provide the first systematic measure of scat decay rate duration for Pan troglodytes schweinfurthii, in Kanyawara, Kibale National Park, Uganda. We used two methods:(1) multiple visits to obtain prospective decay rates (PDR) (N = 96 scats) and (2) a novel approach of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…The effects of time between defecation and sampling have been shown to be minor ( 7 ). Due to the presence of dung beetles, rain, and maggots, ape feces generally do not persist for more than a few days ( 107 ). Furthermore, samples older than 3 days are highly degraded and generally do not yield viable DNA for reliable chimpanzee genotyping ( 108 ).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of time between defecation and sampling have been shown to be minor ( 7 ). Due to the presence of dung beetles, rain, and maggots, ape feces generally do not persist for more than a few days ( 107 ). Furthermore, samples older than 3 days are highly degraded and generally do not yield viable DNA for reliable chimpanzee genotyping ( 108 ).…”
Section: Methodsmentioning
confidence: 99%
“…We found that transition rates to later classes during dung decay vary substantially across the year, and full decay of bison dung takes longer than many other well-studied combinations of ecosystems and herbivore (Table 4, Chapman 2004;Kuehl et al 2007;Phillips et al 2018;Erena, Debella, and Bekele 2019).…”
Section: Discussionmentioning
confidence: 76%
“…For example, captive European Bison defecated 28% less in the winter than in the summer, even with supplemental feed (Eycott et al 2013). For studies that want to convert dung densities to actual population numbers, we recommend that researchers either exercise Erena, Debella, and Bekele 2019;Castle and MacDaid 1972;Rodriguez et al 1998;Phillips et al 2018;Kuehl et al 2007;Tsparid et al 2009;Chapman 2004;Olivier, Ferreira, and caution in using the rate found in this study or determine defecation rates from a larger time span.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation